Hubungan Tingkat Stres dengan Gejala Gastritis Mahasiswa Tingkat IV - Putu Adinda Saraswati; I Gede Putu Darma Suyasa; Idah Ayu Wulandari (Jurnal Gema Keperawatan, 2022)
Stress can affect a person's diet and rest time. This results in hormonal changes in the body and an increase in stomach acid which can gastritis symptoms. Fourth-year Bachelor of Nursing students in ITEKES Bali have a fairly large study load such as participating in laboratory practices, BTCLS training and completing thesis so they are easy to experience stress. This study aims to analyze the relationship between stress levels and gastritis symptoms Fourth-year Bachelor of Nursing students in ITEKES Bali. This study employed a correlative analytic research design with a cross-sectional approach. The population of this study was the fourth-year Bachelor of Nursing students in ITEKES Bali. Total sampling was employed in this study, in which 189 respondents were involved in this study. Data were collected by using the Kessler Psychological Distress Scale (K10) and gastritis symptom questionnaire and analyzed with Pearson Correlation. The study was conducted on 21 February 2022. Among the 189 respondents, the majority were women (85.2%) and aged 21 years old (56.6%). The results showed that 32 respondents (16.9%) did not experience any stress, 47 respondents (24.9%) experienced mild stress, 67 respondents (35.4%) experienced moderate stress, and 43 respondents (22, 8%) experienced severe stress. 113 respondents (59.8%) experienced gastritis symptoms and 76 respondents (40.2%) did not experience gastritis symptoms. There is significant correlation between stress levels and gastritis symptoms of fourth-year Bachelor of Nursing students in ITEKES Bali (r=0.455, n=189, p= 0.001).